Land Right from Below in Nepal and the Role of Land Monitoring: Civil Society Perspective in Converging Equity and Efficiency - Nepali, Purna B. (New Angle: Nepal Journal of Social Science and Public Policy, 2016)
Land issue is complex, dynamic and contentious in Nepal. After Nepal became a democratic country in 1951, land reform has been a highly discussed issue. Slogan like, ‘land to the tiller’ became a popular agenda for each political parties having different understandings and interpretations on land issue specifically during the last decades’ armed conflict (1996-2006). To move ahead in this direction, scientific land reform has been laid a top priority in Comprehensive Peace Agreement 2006, Interim Constitution 2007 and newly promulgated constitution of Nepal 2015 to address equity and efficiency issues. There is a big debate going on equity and efficiency in the country. Realizing strengths of both issues, following analytical framework such as agrarian political economy and democratic and pro-poor land governance, it is found that civil society monitoring is playing a pivotal role in converging equity and efficiency issues of land reform. Such monitoring initiatives generate evidences that serve to exert pressure on effective response by Government to collective demands for justice. By combining equity and efficiency, Nepal’s civil society and citizen-led initiatives are definitively promoting an active engagement of reformist actors and change-makers for generating equitable economic growth. Few determinants of this citizen led initiative are: activism and engagement, clear and articulated demand, efficient and accountable,mechanism and putting voice of vulnerable groups.